(untitled) (Journal of Hama University, 2021)
The aim of this study was to compare the retention of conventional mandibular complete dentures to the mandibular complete dentures having lingual flanges constructed by flexible acrylic resin “Versacryl.” The sample of this study comprised 10 completely edentulous patients. Each patient received one maxillary complete denture and two mandibular complete dentures. One mandibular denture was made of conventional heat‑cured acrylic resin (traditional) and the other had its lingual flanges made of flexible acrylic resin Versacryl. Digital force‑meter was used to measure retention of mandibular dentures at delivery (T1) and at two weeks (T2) and two months (T3) following denture insertion. The statistical analysis showed that at follow‑up appointments, retention of mandibular complete dentures with flexible lingual flanges was significantly greater than retention of conventional mandibular dentures (P = 0.003) in T1, (P = 0.001) in T2 and (P < 0.001) in T3. In both types of mandibular dentures, retention of dentures increased significantly over the follow‑up period. The use of flexible acrylic resin lingual flanges in the making of mandibular complete dentures improved denture retention.